Visual–Tactile Fusion and SAC-Based Learning for Robot Peg-in-Hole Assembly in Uncertain Environments - Jiaxian Tang; Xiaogang Yuan; Shaodong Li (Machines)
Robotic assembly, particularly peg-in-hole tasks, presents significant challenges in uncertain environments where pose deviations, varying peg shapes, and environmental noise can undermine performance. To address these issues, this paper proposes a novel approach combining visual–tactile fusion with reinforcement learning. By integrating multimodal data (RGB image, depth map, tactile force information, and robot body pose data) via a fusion network based on the autoencoder, we provide the robot with a more comprehensive perception of its environment. Furthermore, we enhance the robot’s assembly skill ability by using the Soft Actor–Critic (SAC) reinforcement learning algorithm, which allows the robot to adapt its actions to dynamic environments. We evaluate our method through experiments, which showed clear improvements in three key aspects: higher assembly success rates, reduced task completion times, and better generalization across diverse peg shapes and environmental conditions. The results suggest that the combination of visual and tactile feedback with SAC-based learning provides a viable and robust solution for robotic assembly in uncertain environments, paving the way for scalable and adaptable industrial robots.